Students' Views about the Inclusion of Environmental Education and Education for Sustainability in Teacher Education Courses - Loubser, C.P. (International journal of educational sciences, 2015)
Education can solve many of the burning environmental issues in the world. Universities should play an important role also. This paper will focus on the role teachers, education faculties, colleges and institutions can play in implementing environmental education and education for sustainability. It is argued that provision should be made for environmental education and education for sustainability in curricula for teacher training and those student teachers should be taught how to teach environmental education and education for sustainability in an interdisciplinary way. The skills and knowledge student teachers gain should be assessed during teaching practice visits by lecturers.